AUDIT OF LEARNING MANAGEMENT INFORMATION SYSTEM GOVERNANCE BASED ON GOOGLE CLASSROOM USING THE COBIT 2019 FRAMEWORK (Case Study: Study Group X) - Salsabila Maharani; Thoriq Akbar Rahman Fauzi; Indika Pratama (PT. ZIVANA CENDEKIAWAN BANGSA, 2026)
The rapid development of information technology has encouraged the adoption of digital learning management systems, one of which is Google Classroom, as a primary platform to support teaching and learning activities. However, the effectiveness of its implementation requires proper information technology governance to ensure optimal, secure, and goal-oriented services. This study aims to audit the governance of the Google Classroom-based Learning Management Information System using the COBIT 2019 Framework at Study Group X. The research employed a quantitative descriptive approach, with data collected through observations, interviews, documentation, and questionnaires. The assessment was conducted using relevant COBIT 2019 domains to measure the capability level of IT governance processes. The results indicate that the governance capability level of Google Classroom is at a satisfactory level; however, several gaps remain between the current capability level and the expected target. Therefore, this study proposes recommendations for improving risk management, strengthening system performance evaluation, enhancing documentation, and increasing user competency to support the effectiveness and sustainability of Google Classroom governance.